The kodály method and angklung: an engaging way to enhance music notation reading skills among PGSD students - Hikmawati Usman; Andi Ihsan; Sayidiman; Abidinova Laziza (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2026)
This study examines the effectiveness of implementing the Kodály method, integrated with the Angklung as a learning medium, in enhancing the music notation reading skills of PGSD (Elementary School Teacher Education) students. The research employed a quasi-experimental method with a pre-test-post-test control group design. It involved 30 fourth-semester students from a university in Makassar, who were randomly assigned to experimental and control groups. The research instrument was a music notation reading test validated by an expert. The results indicated a significant improvement in the experimental group, with an average gain score of +31.6 (a 67.7% increase). While the control group showed an average increase of only 11.4% (21.2%). These findings demonstrate that integrating the Kodály method with the Angklung is more effective than the conventional method in enhancing music literacy. This study demonstrates that an experiential, culturally contextual approach is essential in teacher education to develop creative and applicable musical competencies.